An overview of atypical enteropathogenic Escherichia coli - Hernandes, Rodrigo T. [UNIFESP] (2009)
The enteropathogenic Escherichia coli (EPEC) pathotype is currently divided into two groups, typical EPEC (tEPEC) and atypical EPEC (aEPEC). the property that distinguishes these two groups is the presence of the EPEC adherence factor plasmid, which is only found in tEPEC. aEPEC strains are emerging enteropathogens that have been detected worldwide. Herein, we review the serotypes, virulence properties, genetic relationships, epidemiology, reservoir and diagnosis of aEPEC, including those strains not belonging to the classical EPEC serogroups (nonclassical EPEC serogroups). the large variety of serotypes and genetic virulence properties of aEPEC strains from nonclassical EPEC serogroups makes it difficult to determine which strains are truly pathogenic.